Effectiveness of Female Head Teachers Managerial Skills in Improving Teachers Performance (Journal of Social Sciences Review, 2023)
This paper intends to examine public secondary school head teachers competencies and their influence on teacher’s instructional decisions as well the overall school culture. This research paper endeavor to unravel secondary school principal’s managerial competencies and their influence on the performance of secondary school principals and such influence will help to stimulate and transform sophisticated school environment that will make strengthen student’s cognitive, affective as well psychomotor domains. Current study will cover following objective: “To determine the effectiveness of head teacher’s managerial skills on teacher’s academic performance at secondary school level”. Research design utilized for this study is of descriptive qualitative nature. Respondents of the study were secondary school principals/head Masters and secondary school teachers. Population of this research composed of all the 83 females’ secondary and 37 higher secondary schools. Sample of the study extracted from the population were 60 principals/ head masters and 120 secondary school teachers. Through proper consultation the researchers developed data collection instrument titled: “Principals’ Managerial Skills Scale”. Mean, Standard deviation was employed as a statistical data analysis tools. Data analysis was followed by conclusion to render realistic recommendations for the establishment of sophisticated school management.
Keywords: School Achievements; Managerial Skills; Teacher performance